ANALISIS KESULITAN BELAJAR SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DENGAN METODE POLYA PADA MATERI PECAHAN KELAS V SD NEGERI 1 DOPLANG - Diana Puji Lestari; A.Y. Soegeng Ysh; Joko Sulianto (STKIP Subang, 2023)
The background that drives this research is that in learning math problem solving students are still not able to work on problem solving problems properly. The purpose of this study was to describe what are the learning difficulties in solving mathematical problems using the Polya method on fractional material experienced by fifth grade students at SD Negeri 1 Doplang and to find out the factors that influence learning difficulties in solving mathematical problems using the Polya method on fraction material for fifth grade elementary school students. Country 1 Doplang. This type of research is descriptive qualitative. Using, test methods, observations, interviews, questionnaires and documentation. The results showed that students' learning difficulties in solving math problems using the polya method in class V fraction material at SD Negeri 1 Doplang had a score on the aspect of understanding the problem as much as 287 (11%), making plans had a score of 283 (10.8%), carrying out the plan has a score of 516 (19.8%) and rechecking answers has a score of 166 (6.3%). Factors that cause students to experience learning difficulties in solving mathematical problems with the polya method in class V fraction material at SD Negeri 1 Doplang consist of physical factors, motivational and attitudinal factors, environmental factors, teaching teacher variation factors, and school infrastructure factors.